Kajian Analisis Geometri pada Rumah Adat “Dori Mpulor” Sebagai Dasar Pengembangan Pembelajaran Matematika Berbasis Etnomatematika - Ellissi, Wike; Liliana, Sepriani; Tutui, Helbi (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to examine the geometric concepts present in the traditional house "Dori Mpulor" as a basis for developing ethnomathematics-based mathematics learning to support the Merdeka Curriculum. The study employed a qualitative descriptive method with an ethnographic approach. Data collection techniques included observation, interviews, and documentation. The analysis of the data was performed using qualitative techniques, including data reduction, data display, and conclusion drawing. The findings revealed that there are geometric concepts in the structure of the Dori Mpulor Traditional House, which include the positioning of two lines on a plane (parallel lines, intersecting lines), angles (opposite angles, supplementary angles, right angles, and acute angles), gradients, congruency (line segments, angles, polygons), polygon similarity, triangles (equilateral and right triangles), circles, cylinders, parallelograms, and trapezoids. In conclusion, the study of geometric concepts in the Dori Mpulor Traditional House can be implemented as learning material, giving educators the freedom to create quality learning experiences tailored to students' needs within a real context, so that students gain enjoyable and meaningful learning experiences. Keywords: Ethnomathematics; Geometric; The traditional house.